The role of e-banking as a marketing tool - Maurice Ayuketang Nso (Innovative Marketing)
Banks and financial services providers can make use of electronic tools in marketing their products and services. The role of e-banking as a marketing tool has not generated a lot of interests by scholars and researchers in this area. This paper examines and discusses the usage of e-banking in marketing the products and services of banks. It illustrates that e-banking could be used for marketing by banks, financial institutions and services providers, and other businesses. Putting together techniques on ebanking, marketing and technology, there is a favorable tri-existence of cross and up selling, cross-marketing and cross cost cutting advantages for financial services providers using e-banking tools in marketing activities. Using Chi-square technique to testthe hypothesis, the paper affirms that e-banking can be used as a marketing tool in marketing the products and services of banks and financial services providers. Three questions were ditched out to students who have at least studied a course in e-banking, marketing of financial services and/or researched on digital banking, thus underlining the respondents’ acquaintances with and knowledge in e-banking concepts as key in the research. Students – of course young, whatsapps and Google classroom media used to collect data are attributes that entertain favorably the application of e-banking as marketing tool.